Innovative Procurement Adoption for Industrialised Building System (IBS) Projects - Liyana Binti Tajul Ariffin, Hamizah; Yeo Hooi Lynn, Brenda; Binti Mohamad Shukery, Nurshikin; Binti Abdul Rahiman, Nafisah; Hendra Bin Mahmud, Syamsul; Binti Mohd Raslim, Faraziera (International Journal of Engineering and Technology, 2018)
Industrialised Building System [IBS] is a new method that used prefabrication components in building construction as an alternative towards enhancing construction performance.  The Construction Industry Development Board [CIDB] embraced the IBS method to enhance productivity and building quality, reduce wastage on site, increase occupational safety and health, and reduce overall cost of construction.  Currently, most of the IBS project developments in Malaysia are still adopting traditional procurement system.  However, traditional procurement system has been criticised for its fragmented procedure to project delivery in terms of integration and collaboration of the project team.  As a result of that problem, a number of issues have recently arisen such as reworks, time delay, rising costs, lack of communication and coordination, and wastages.  The purpose of this research is to identify challenges of the current procurement system and to investigate the possibilities of implementing innovative type of procurement method for IBS implementation.  A deductive research approach was adopted.  Reviewing relevant literature before embarking into any academic research project is one way of exploring a known theory in a holistic manner.  It also appears to be one of an essential feature to create a firm foundation for the research.  Based on extensive literature reviews; this paper describes what are initiatives that have been taken from developed nations which are known as earlier IBS adopters and through the findings these experiences may shed some light on the type of procurement that have been adopted.  This study was conducted among Grade 7 IBS contractors in Malaysia to gain further clarification on the immensity of the issues as well as assessing the research instrument.  The findings from this study reveal that financial matters, lack of early involvement, lack of integration and coordination, knowledge and understanding, role and responsibility, risk liability, communication and information, attitude and relationship matters are challenges embedded in the existing procurement approach in adopting IBS.  Suggestion on how innovative type of procurement method such as Separation of IBS from Main Contract, Partnering and Integrated Project Delivery [IPD] will be able to minimise the fragmentation gaps will be concluded.